Prevalence and determinants of anxiety and depression among children and adolescents undergoing cancer treatment at a tertiary hospital in a resource-limited setting - Misikir Tesfaye Dirre; Elias Tesfaye; Alemayehu Negash Torba; Bezaye Alemu Tsegaye; Yonas Tesfaye; Mubarek Abera Mengistie; Milki Tufa Feyisa; Puturos Puturos Reta; Tadios Teka Bireda; Tamirat Godebo Woyimo (Medicine, 2026)
Childhood cancer significantly impacts the mental health and overall well-being of children and adolescents. Mental health issues, such as depression and anxiety, are common among these children. These conditions can lead to long-term consequences, including poor psychosocial functioning, an increased risk of substance misuse, and chronic mental and physical health problems. This study assesses the prevalence of anxiety and depression, along with associated factors, among children and adolescents undergoing treatment for cancer at a tertiary center in Ethiopia in 2024. An institution-based cross-sectional study was conducted involving 206 consecutively selected children and adolescents. Data were collected from March 1 to May 13, 2024. Anxiety and depression were screened using the Revised Child Anxiety and Depression Scale. A consecutive sampling technique was employed. The Kobo Toolbox was used to collect data, which were then exported to the Statistical Package for the Social Sciences version 26.0 for analysis. Logistic regression analysis was performed to identify factors associated with anxiety and depression, with statistical significance declared at P < .05. Odds ratios and 95% confidence intervals (CI) were calculated to determine the presence and strength of associations. A total of 203 respondents participated in this study, resulting in a response rate of 98.6%. The overall prevalence of depression and anxiety was 39.4% (95% CI: 33–46%) and 45.3% (95% CI: 38–52%), respectively. Significant associations with depression were found for the following factors: age (13–18; adjusted odd ratio [AOR] = 2.62, 95% CI: 1.29–5.32), hospitalization duration >4 weeks (AOR = 3.31, 95% CI: 1.23–8.88), and illness duration exceeding 24 months (AOR = 3.22, 95% CI: 1.06–9.73). In addition, corticosteroid medication (AOR = 3.69, 95% CI: 1.21–11.22), comorbid illness (AOR = 2.81, 95% CI: 1.26–6.25), and severe pain (AOR = 3.69, 95% CI: 1.21–11.21) were significantly associated with anxiety. The prevalence of anxiety and depression among children and adolescents undergoing treatment for cancer is high. Therefore, early screening and intervention are necessary, particularly for those aged 13 to 18, those hospitalized for more than 4 weeks, those with illness durations exceeding 24 months, and those experiencing comorbid illnesses, severe pain, or receiving corticosteroid medication.